Need Analysis for English Writing Syllabus Development - Rosi Fitriyanti S; Lewi Kabanga; Emon Paranoan (Journal on Education, 2023)
This study aims to identify the students’ needs in learning English writing in promoting syllabus development of writing skills. This research was a qualitative descriptive research. The subjects of this research were 45 students of the fifth semester of non-English Study Program, analyst department of Jayapura Sciences and Technology University. The data were collected using a questionnaire with the media of virtual meeting and what’s up Group. The analysis of data based on the theoretical framework that revealed in every detailed questions. The results found that students target of studying English writing are for their future profession and for their higher education. They want enjoying a Writing practice for activities at the classroom together with their pair or group. The students assumed for the role of teacher as a facilitator and guide in the teaching learning activities. Students also enjoy conducting writing by using media such as picture. Beside that they do not like to learn grammar directly but they like to learn by recognizing the error of sentence and completing the missing text.